2002
DOI: 10.1097/00003226-200211000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Daunorubicin Versus Conjunctival Autograft in Primary Pterygium Surgery

Abstract: We conclude that intraoperative daunorubicin (0.02%) and conjunctival autograft are both equally effective adjuncts to pterygium surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…6 Although the antifibroblastic action of DNR has been known for over two decades, its safety in various ophthalmic surgeries has been demonstrated in the last decade. DNR has increasingly been used to improve the success rate of ocular surgeries, including strabismus surgery, 7 pterygium surgery, 8 retinal detachment surgery, 9 and in the prevention of PCO following cataract extraction. 10,11 Dadeya et al 16,6 evaluated the safety and efficacy of intraoperative 0.02% DNR in strabismus surgery and pterygium surgery.…”
Section: Daunorubicinmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although the antifibroblastic action of DNR has been known for over two decades, its safety in various ophthalmic surgeries has been demonstrated in the last decade. DNR has increasingly been used to improve the success rate of ocular surgeries, including strabismus surgery, 7 pterygium surgery, 8 retinal detachment surgery, 9 and in the prevention of PCO following cataract extraction. 10,11 Dadeya et al 16,6 evaluated the safety and efficacy of intraoperative 0.02% DNR in strabismus surgery and pterygium surgery.…”
Section: Daunorubicinmentioning
confidence: 99%
“…Daunorubicin (DNR) is a glycosidic antimetabolite that inhibits fibroblast proliferation in vitro and in vivo. 6 The antifibroblastic action of DNR has been used both in animal studies and in human subjects to improve the success rate of various ophthalmic surgeries, including strabismus surgery, 7 pterygium surgery, 8 and retinal detachment surgery, 9 and in the prevention of posterior capsular opacification (PCO) following cataract extraction. 10,11 In glaucoma, DNR has been used experimentally and in human subjects to improve the success rate of high-risk GFS by way of a biodegradable slow-release subconjunctival (s/c) implant, as preoperative and postoperative s/c injections following trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, they found complications like pyogenic granuloma in 5.5%, graft oedema in 2.77% loose graft in 2.77 % and dellen formation in 2.77%. 21 In group2 patients three (10%) patients developed chemosis and four (13.3%) patient had delayed epithelialisation.…”
Section: Discussionmentioning
confidence: 93%
“…In his study minor complications like conjunctival graft oedema, Pyogenic granuloma, epithelial inclusion cyst formation, retraction and necrosis of graft was present, 14 which almost matches with my study. Dadeya et al (2002) conducted a study on conjunctival autograft. In their study, they found complications like pyogenic granuloma in 5.5%, graft oedema in 2.77% loose graft in 2.77 % and dellen formation in 2.77%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation